Confiabilidade da fotogrametria na medida do deslocamento vertical da alçada de egg no nado sincronizado - Carvalho Guerreiro, R.; Peixoto César, E.; Périllier, R.; Assis, C. A.; Meireles Santos, T. (Revista Brasileira de Ciência e Movimento, 2013)
Boost is a typical technique of the synchronized swimming, characterized by the projection of the athlete up, where the vertical displacement is an important factor in performance judgment. For their practical applicability and accuracy, the photogrammetry method was chosen for determine the vertical displacement. The objective was to calculate the reliability within and between judges of the method and measure of vertical displacement during the boost. Participated ten athletes of the Synchronized Swimming Brazilian team (20.9 ± 2.3 years; 163.1 ± 4.5 cm; 56.0 ± 4.4 kg and 19.0 ± 3.1% body fat). To determine the reliability were used the intra-class correlation and the typical error of measurement (TEM) absolute and relative. The method presented ICC of 0.995 and 0.993, within and between judges, respectively, with TEM of 0.5% for both. In internal consistency was found an average ICC 0.94 ± 0.03 and TEM 0.34% ± 0.07%, and stability met mean ICC 0.87 ± 0.04, ETM 0.49% ± 0.06%. We conclude that the method presented high values within and between judges and the measured presented values moderate to stability and high for internal consistency.